Financial Performance Analysis of The Acquiring Companies 2010-2012 - Brazally, Andrian Risjad; Prasetyo, Andrian Budi (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2023)
This study was conducted to analyze the company's performance before and after the acquisition, the differences and their effect on stock value. Probability Ratio, Efficiency Ratio, Liquidity Ratio, and Leverage Ratio is used to measure the company’s performance while the Stock Value is reflected by Earning Per Share (EPS). The sample is company listed on Indonesia Stock Exchange (IDX) that consists of 32 companies that made acquisitions in the year 2010-2012 with data available 5 years before and 5 years after the acquisition or year 2005-2017. To analyze the data sample, this study uses paired t-test and multiple linear regression analysis that resulted in a significant and positive change in the ratio of Probability Ratio, Efficiency Ratio, and Liquidity Ratio in the company before and after the acquisition and a significant influence on the Profitability Ratio on Stock Value.